The Impact of ChatGPT on EFL University Students’ Writing Skills: A Systematic Literature Review - Ni Nengah Dina Juliani; I G A Lokita Purnamika Utami; Ni Nyoman Artini (Pusat Riset dan Inovasi Nasional, 2026)
Writing is an important skill for university students who study English as a Foreign Language (EFL), but it is often difficult to master in academic contexts due to linguistic and cognitive challenges. Recently, Artificial Intelligence (AI) tools, for example like ChatGPT, have gained significant popularity in language learning and academic writing support. Through a Systematic Literature Review (SLR), this study analyses existing research related to the impacts of ChatGPT on writing skills of university students in the EFL context. Using the PRISMA guidelines, the study reviews eleven relevant articles published between 2023–2026 from various academic databases. The results examined that ChatGPT helps students improve different aspects of writing, such as organization, grammar accuracy, vocabulary use, coherence, and overall writing quality. It also increases students’ motivation, confidence, and ability to learn independently by providing quick, accessible, and personalized feedback during the writing process. However, the results also examined several challenges of using ChatGPT as a writing tool, such as academic dishonesty, inaccurate or misleading information, and students’ overreliance on AI tools, which may reduce critical thinking and writing autonomy.